Kinerja Beberapa Bank Syariah Berdasar Tingkat Efisiensi Melalui Pengukuran DEA - Pinaestri Cahyaningsih; Didit Purnomo; Harun Harun; Maulidyah Indira Hasmarini (Universitas Muhammadiyah Magelang, 2017)
The purpose of this research is to find out the efficiency of Islamic Banking in 2015-2016 period. Samples both input and output from 4 Islamic Banking were used in this research included deposit, asset, personnel load, financing, and operational profit. Every changes of variable in that data can show the condition of Islamic Banking. The method uses in this research is called by Data Envelopment Analysis (DEA) with intermediation approach. The result shows that only Bukopin Islamic Banking and BNI Islamic Banking who have reached 100 percent efficiency during this research period. The highest inefficiency is experienced by Mandiri Islamic Banking. Mandiri Islamic Banking was insufficiency during this research period. Meanwhile, the BCA Islamic Banking underwent inefficiency three times in 2016